PENENTUAN DAERAH RESAPAN SISTEM PANAS BUMI GUNUNG WAYANG WINDU, JAWA BARAT - FAJAR HENDRASTO, RADEN
Wayang Windu is one of productive geothermal fields in West Java which is dominated by two phase reservoir system. Until 2003, 30 wells had been drilled and used to support a unit of 110 MWe geothermal electricity power plant. The origin of fluids and recharge area are important information in managing the geothermal system, i.e. to understand the interaction and relation between reservoir and the fluid resources. The interpretation of stable isotope (d18O and d2H) data provides some information to determine recharge area, movement and distribution of fluid that infiltrates into the reservoir. This interpretation shows that Wayang Windu geothermal fluid system originates from meteoric water, and there are two recharge areas, i.e: recharge area for geothermal reservoar (production well and fumarole) and recharge area for hot spring. Infiltration of meteoric water into reservoir occurs in the elevation range of 1,317m to 1,606 m above sea level (asl). More permeable lithology in that particular elevation range seems to be located in the western and northwestern parts of the research area. Recharge area for hotspring is situated at the elevation range of 1,987m to 2,837m (asl), where the lithologic characteristic in the northern area seems to be more permeable than in the central area. Steam phase of the geothermal fluid occures through boiling process with a change in the isotopic composition, and ascend to the surface as fumarole, while geothermal fluid which is extensively diluted or mixed with meteoric water emerges on the surface as hotspring. Important areas for recharge conservation are the areas around Pangalengan, Situ Cileunca, G. Haruman, G. Puncak Besar, Malabar Tea Plantation, and Cibolang. The information about recharge area is useful for Wayang Windu geothermal field management to maintain the material balance between water recharge and the produced fluid by carrying out conservation on the surface, so that ground water, as a source of recharge, can be sustained.